Teaching grammar in French as a foreign language-classes in macedonian schools - Kasaposka-Chadlovska, Milena (St. Kliment Ohridski University, Faculty of Education-Bitola, 2020)
In our many years of experience teaching the French language, we have had more cases of students with low grammatical knowledge of the language as opposed to those with solid grammatical basis, although most frequently, both of those groups of students have already been learning the language in the primary and secondary school. This reality inspired us to set a goal to use this research to investigate whether this “problem” could possibly be a result of the methodology used to teach the grammar in the lower education levels. Namely, our intention was to gain insight in the way the grammar is taught in a part of the Macedonian primary and secondary schools. For that purpose, we prepared a questionnaire through the answers of which we gained knowledge about several aspects of teaching grammar. In general, the research has shown that explicit grammar is used, in principle, but that it is not taught in a completely traditional way, but through a deductive approach. In doing so, the teachers rarely use a specialized pedagogical grammar for French as a foreign language, mostly relying on the grammar offered in the schoolbook. We have also reached a conclusion that there is big room for specialized training of a large part of the teachers, on the topic of grammar methodology of teaching in French as a foreign language. Apart from this, the research also points at some other defects which need to be resolved in the future if we want to achieve better quality of the classes and more success among the students who are taught the French grammar.
Keywords: methodology of teaching, grammar, French language, primary education, secondary education.